2014
DOI: 10.2527/jas.2014-7621
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics in the ruminal microbiome of dairy cows during the transition period

Abstract: The transition period in dairy cows refers to the period from 3 wk before calving to 3 wk post-calving and is a critical time for influencing milk production and cow health. We hypothesize that the ruminal microbiome shifts as dairy cows transition from a non-lactation period into lactation due to changes in dietary regimen. The purpose of this study was to identify differences in the ruminal microbiome of primiparous and multiparous (study group) cows during the transition period. Five primiparous and 5 multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
105
5
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 44 publications
22
105
5
4
Order By: Relevance
“…In contrast, the Enterobacteriales order was highly prevalent in composite cattle wastewater samples. This is not in agreement with a previous study that reported that Firmicutes was the most abundant phylum across all communities in dairy cows (65). Such a discrepancy could be due to the fact that we collected cattle wastewater samples from wastewater drains in abattoirs, whereas Pitta and colleagues (65) collected ruminant contents from the stomachs of dairy cows.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, the Enterobacteriales order was highly prevalent in composite cattle wastewater samples. This is not in agreement with a previous study that reported that Firmicutes was the most abundant phylum across all communities in dairy cows (65). Such a discrepancy could be due to the fact that we collected cattle wastewater samples from wastewater drains in abattoirs, whereas Pitta and colleagues (65) collected ruminant contents from the stomachs of dairy cows.…”
Section: Discussioncontrasting
confidence: 54%
“…Succiniclasticum (3.53; 1.52%) and Succinivibrio (0.26; 0.01%), represented differences between the PacBio V1-V8 and Miseq V1-V3 amplicons (P b 0.05), which have been identified in the rumen at abundances greater than 0.1% (Myer et al, 2015a;Pitta et al, 2014).…”
Section: Taxonomic Compositionmentioning
confidence: 99%
“…In comparison to some studies, where bacterial communities were dominated by Bacteroidales, and specifically its genus Prevotella (Jami et al, 2013;Pitta et al, 2014), in the present study multiple orders of bacteria have a sizable relative abundance. Such more diverse bacterial communities appear to be more common globally , and is likewise reported by Wang et al (2012), Petri et al (2013) and Lima et al (2015).…”
Section: Ration Effects On the Relative Abundance Of Bacterial Communcontrasting
confidence: 67%
“…Various studies addressed this relationship between ration composition and the composition of the rumen microbiota (review by McCann et al, 2014). However, few studies (Mohammed et al, 2012;Pitta et al, 2014;Lima et al, 2015) focused on the transition period in dairy cattle. Unfortunately, these studies generally provide very little information about feed intake and no studies have reported peripartum changes in papillae morphology, VFA absorption capacity, and their relationship to the changes in the microbiota.…”
Section: Changes In the Composition Of The Rumen Microbiota Communitymentioning
confidence: 99%
See 1 more Smart Citation